2011
DOI: 10.1094/fg-2011-0126-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stage Influences Forage Yield and Quality of Winter Rye

Abstract: Winter rye (Secale cereale L.) is a common cover crop in the Upper Midwest United States with potential as a forage crop; but little is known about the effect of maturity on its spring forage yield and quality. Our objective was to determine the forage yield and quality of three winter rye cultivars at six different maturities in four environments. The yield response to increased maturity was quadratic and variable over environment with ranges at boot (Zadok 41) of 1.2 to 2.7 tons/acre, at heading (Zadok 51) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 18 publications
8
24
0
Order By: Relevance
“…The year × treatment interaction was significant, with the greatest difference in rye DM yield between ER and LR treatments occurring 2009. The much greater rye DM yield with only 2 wk of additional growth in the LR treatment supports the work of Kantar et al (2011), who reported that winter rye DM yield rapidly increased from mid to late May in Minnesota.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The year × treatment interaction was significant, with the greatest difference in rye DM yield between ER and LR treatments occurring 2009. The much greater rye DM yield with only 2 wk of additional growth in the LR treatment supports the work of Kantar et al (2011), who reported that winter rye DM yield rapidly increased from mid to late May in Minnesota.…”
Section: Resultssupporting
confidence: 83%
“…Often producers are reluctant to plant winter rye because of costs associated with rye management, but when harvested, rye can provide high quality forage (Kantar et al, 2011) and possibly offset the cost of production. Rye is the preferred small grain in a double‐crop system because it reaches optimum growth stage earlier in the spring than other small grains (Maloney et al, 1999), allowing for earlier harvest and subsequent corn planting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the presence of Kura clover in mixtures increased CP and IVTD and reduced NDF concentration compared to monoculture cereals. Our findings are consistent with other research on winter cereals reporting declining forage CP, IVTD, and NDFD and increasing NDF with maturity (Andrzejewska et al 2014;Kantar et al 2011;.…”
Section: Forage Nutritive Valuesupporting
confidence: 93%
“…Perennial legume forages are susceptible to winter kill in cold weather locations, but the winter hardiness of rye helps ensure adequate spring forage (10). A companion paper to this study quantifies rye forage quality and yield at various growth stages, and offers management recommendations to optimize rye production (13).…”
Section: Introductionmentioning
confidence: 99%